2013
DOI: 10.1002/jaba.3
|View full text |Cite
|
Sign up to set email alerts
|

Persistence During Extinction: Examining the Effects of Continuous and Intermittent Reinforcement on Problem Behavior

Abstract: This study examined behavioral persistence during extinction following continuous or intermittent reinforcement in the context of an analogue functional analysis of problem behavior. Participants were four children diagnosed with an autism spectrum disorder who engaged in problem behavior; and for whom functional analyses indicated sensitivity to social reinforcers. Experimental sessions included four successive 5-min components: No social interaction, continuous or intermittent reinforcement for problem behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…Knowledge of behavioral function also was essential for studying the relation between reinforcement schedule and resistance to extinction. Consistent with behavioral momentum theory, MacDonald, Ahearn, Parry‐Cruwys, Bancroft, and Dube () found that problem behavior was more resistant after continuous reinforcement than after intermittent reinforcement. Such an outcome suggests that behavior may be easier to treat in the natural environment, where reinforcement is typically delivered on an intermittent basis.…”
Section: Articles In the 2013 Special Issuementioning
confidence: 80%
“…Knowledge of behavioral function also was essential for studying the relation between reinforcement schedule and resistance to extinction. Consistent with behavioral momentum theory, MacDonald, Ahearn, Parry‐Cruwys, Bancroft, and Dube () found that problem behavior was more resistant after continuous reinforcement than after intermittent reinforcement. Such an outcome suggests that behavior may be easier to treat in the natural environment, where reinforcement is typically delivered on an intermittent basis.…”
Section: Articles In the 2013 Special Issuementioning
confidence: 80%
“…We are aware of only one clinical study that approximates a test of one of the BMT paradigms of treatment relapse. MacDonald, Ahearn, Parry‐Cruwys, and Bancroft () conducted a clinical translation of the resurgence paradigm of relapse described by Podlesnik and Shahan () with some variation from the basic research. In the first phase of the study, problem behavior was alternately reinforced on a CRF schedule and a variable‐ratio (VR) 3 schedule in separate components of a mixed schedule of reinforcement.…”
mentioning
confidence: 99%
“…Hanley (2012) asserts that the use of FR-1 schedules may be important for functional analyses because those schedules reduce the frequency and severity of the problem behavior. However, FR-1 schedules may also increase the momentum of problem behavior, making it more resistant to subsequent intervention (MacDonald, Ahearn, Parry-Cruwys, Bancroft, & Dube, 2013). Further, the use of a schedule markedly different than what is in place naturally may affect the validity of the assessment.…”
Section: Is It Feasible To Conduct the Functional Analysis?mentioning
confidence: 99%